Uma sequência didática sobre porcentagem e tratamento da informação utilizando problemas das OBMEP - Faxina, Maria Lúcia Beltrami (Universidade Federal de São Carlos, 2016)
This work presents a didactic sequence, in thirteen activity pages, with problems on percentage and information processing of the Brazilian Mathematics Olympiad of Public Schools (OBMEP), idealized for different learning from the traditional exposition of theory followed by examples and exercises. The work was developed with the 8th grade classes of a municipal school in the city of Campinas in the year 2015. The activities were designed with the objective of giving the students autonomy to solve problems in everyday situations in the various areas of knowledge, always rescuing contents to make the connection between the new and the old knowledge. In application dynamics, we tried to diversify the presentation of content through play activities. The evaluation was carried out in multiple moments’ ant we consider that the presented results can contribute significantly to the improvement of basic education especially in the ways of approaching new contents in the teaching of Mathematics.
Keywords: Problem solving; Information processing; Percentage; Fraction; Graphs; Resolução de problemas; Tratamento da informação; Porcentagem; Fração; Gráficos; OUTROS